Subdural Anesthesia as a Complication of an Interscalene Brachial Plexus Block: Case Report. Issue 5 (September 1994) - Tetzlaff, John E.; Yoon, Helen J.; Dilger, John; Brems, John
Abstract : Background and Objectives: Interscalene brachial plexus block is performed in the groove between the anterior and middle scalene muscles at the level of C6, just over the transverse process. Injection occurs within 1-2 cm of the dural sleeve and could be misdirected into the epidural, subdural, or subarachnoid spaces. Methods: Interscalene block was performed by elicitation of paresthesia with 40 mL 1.4% mepivacaine, 1/200, 000 epinephrine. Results. Initially, complete interscalene block was achieved that evolved into apnea, high motor, and sensory block; requiring induction of general anesthesia. Conclusions: The case represents a partial injection of local anesthetic intended for the interscalene brachial plexus into the subdural space. The diagnosis is based on the normal evolution of the block into full motor and sensory anesthesia of the ipsilateral brachial plexus that evolved into a patchy, sensory, and motor block involving many dermatomes outside the brachial plexus, with minimal sympathetic block, and evidence of a normal interscalene block on emergence from general anesthesia. Subdural injection must be considered when unusual motor and sensory block occurs after interscalene block, especially after a time interval too long for epidural or subarachnoid injection, or with minimal evidence of sympathetic block, after suspected high central block injection.